A case study for measurement uncertainty of heavy metal analysis in drinking water with inductively coupled plasma-mass spectrometry (ICP-MS). Issue 25 (10th June 2016) - Tunç Dede, Özlem
Abstract : The measurement uncertainty related to the analysis of eight trace elements (Pb, Zn, Cr, Mn, Cu, Cd, Hg and As) in drinking water using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) was evaluated in detail. Abstract : The measurement uncertainty related to the analysis of eight trace elements (Pb, Zn, Cr, Mn, Cu, Cd, Hg and As) in drinking water using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) was evaluated in detail. The evaluation section included three steps. Firstly, the major contributions to the uncertainty budget (purity of calibration standards, volume, precision, recovery and calibration curve) were identified. The dominant contributions to uncertainty were found to be the calibration curve and the method recovery. In the second step, the measurement uncertainty values for all individual components that contribute to the uncertainty budget were determined and the components were assembled to get a combined standard measurement uncertainty. The last step involved the calculation of expanded measurement uncertainties by multiplying the combined standard measurement uncertainty by a coverage factor k ( k = 2.0 at 95% level of confidence). The expanded measurement uncertainties for the eight trace elements were calculated as ( C Pb ± 0.17) μg L −1, ( C Zn ± 0.14) μg L −1, ( C Cr ± 0.12) μg L −1, ( C Mn ± 0.11) μg L −1, ( C Cu ± 0.11) μg L −1, ( C cd ± 0.70) μg L −1, ( C Hg ± 0.46) μg L −1, ( C As ± 0.48) μg L −1, with k = 2 for all elements. All measurement uncertainty values were found to be below 50% of the values given in the relevant environmental quality standards.